2016
DOI: 10.1186/s12974-016-0768-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of effector function of CNS autoreactive CD4 T cells through inhibitory receptors and IL-7Rα

Abstract: BackgroundMultiple sclerosis (MS) is a chronic CNS autoimmune disease characterized by inflammation, demyelination, and neuronal degeneration, where myelin-specific CD4 T cells play critical roles in the formation of acute MS lesions and disease progression. The suppression of IL-7Rα expression and the upregulation of inhibitory receptors (PD-1, etc.) are essential parts of the cell-intrinsic immunosuppressive program regulating T effector functions to prevent autoimmunity. However, little is known on the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The PD-1 is an important immune checkpoint role that negatively regulates T effector function and EAE development (Carter et al , 2007, Nuro-Gyina et al , 2016). Therefore we compared the expression of PD-1 and its ligand, PD-L1, in myelin-specific CD4 T effector cells from immunized CKO mice and WT littermates during priming phase and effector phase of EAE.…”
Section: Resultsmentioning
confidence: 99%
“…The PD-1 is an important immune checkpoint role that negatively regulates T effector function and EAE development (Carter et al , 2007, Nuro-Gyina et al , 2016). Therefore we compared the expression of PD-1 and its ligand, PD-L1, in myelin-specific CD4 T effector cells from immunized CKO mice and WT littermates during priming phase and effector phase of EAE.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that IL-7 can support immune-cell reconstitution in lymphopenic conditions [ 22–25 ], restore sepsis-induced lymphocyte dysfunctions ([ 37 , 38 ]), enhance effector function of autoreactive T cells [ 8–13 ], and expand tumor-reactive T cells [ 29 , 30 ]. We then asked whether pathogen-reactive T cells also benefited from IL-7 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, IL-7 is expressed in inflamed tissues of patients with (rheumatic) autoimmune diseases, where it can be produced by several cell types [ 43 ] (including macrophages, dendritic cells, and fibroblasts) and favor pathogenic Th1- and Th17-associated cytokine secretion. Furthermore, dysregulated IL-7 expression or activation of CD127 were found in patients with autoimmune conditions [ 8–13 ], suggesting that IL-7 supports the function of pathogenic effector cells in autoimmunity. In agreement with this, blocking the IL-7R in experimental animal models ameliorated autoimmune disease manifestations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Nuro‐Gyina et al . ). Neuroprotective microglia/macrophage cells are found more than damaging microglia/macrophage cells during the early phase in acute EAE but damaging microglia/macrophage cells become abundant during peak and recovery phase of EAE (Ahn et al .…”
mentioning
confidence: 97%